Mobility policies for sustainable development - Leite, Joana Ribau Esteves Neves (2020)
The present dissertation was built from the need to increase sustainability in the populations’ habits, including their commuting habits. The existing policies and services should provide the user with the needed mobility without compromising the environment. The dissertation aims at analysing the existing global and European policies for sustainable development and sustainable urban mobility, and at understanding their applicability at the local level. The case of study is the city of Aveiro, which is a mid-sized city situated in the Centre Region of Portugal. This city presents a high level of private car use and this analysis aims at evaluating if the Urban Mobility Plans are aligned with the proposed at the global and European levels. Thus, the 2030 Agenda for Sustainable Development of the United Nations was analysed. Then, the 2011 White Paper – “Road to a Single European Transport Area” of the European Commission and the Sustainable Urban Mobility Plans’ Guidelines of the European Commission were analysed. Moreover, the analysis of the socio-economic factors of Aveiro was pursued, as well as the commuting habits of the citizens living and working in the city. Finally, Aveiro’s Sustainable Urban Mobility Plan was evaluated, as was its fitting into the aforementioned global and European policies. In conclusion, Aveiro presents a strategy aligned with the European policies and the Sustainable Development Goals. In order to empower the existing local policies, a model of Mobility as a Service is proposed.